2010
DOI: 10.5551/jat.3038
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Exploratory Efficacy of the Novel Thrombin Receptor (PAR-1) Antagonist SCH530348 for Non-ST-Segment Elevation Acute Coronary Syndrome

Abstract: Aim: A previous phase 2 study of patients undergoing non-urgent PCI treated with SCH530348 plus aspirin and clopidogrel tended to reduce MACE without increased bleeding. This study evaluated the safety of SCH530348 in Japanese patients with NSTE ACS. Methods: Subjects (117), in whom PCI was planned, received standard-of-care (aspirin, ticlopidine, and heparin) and were randomized 4:1 to receive either SCH530348 (20 or 40 mg loading dose followed by 1 mg/d or 2.5 mg/d for 60 days) or placebo. The key safety end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
74
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 21 publications
5
74
0
Order By: Relevance
“…Consistent with the results from main phase III trials, vorapaxar led to significantly increased risk of major bleeding events, including ICH [11,12]. In the phase II studies involving patients undergoing PCI, vorapaxar demonstrated a trend towards lesser thrombotic events compared to placebo without exposing to an increase in bleeding risk [6,9]. It was postulated that while inhibiting thrombin-mediated platelet activation, PAR1 antagonism might not interfere with the hemostatic pathway and, thus, not predispose to a higher bleeding risk [6,9].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Consistent with the results from main phase III trials, vorapaxar led to significantly increased risk of major bleeding events, including ICH [11,12]. In the phase II studies involving patients undergoing PCI, vorapaxar demonstrated a trend towards lesser thrombotic events compared to placebo without exposing to an increase in bleeding risk [6,9]. It was postulated that while inhibiting thrombin-mediated platelet activation, PAR1 antagonism might not interfere with the hemostatic pathway and, thus, not predispose to a higher bleeding risk [6,9].…”
Section: Discussionsupporting
confidence: 70%
“…In the phase II studies involving patients undergoing PCI, vorapaxar demonstrated a trend towards lesser thrombotic events compared to placebo without exposing to an increase in bleeding risk [6,9]. It was postulated that while inhibiting thrombin-mediated platelet activation, PAR1 antagonism might not interfere with the hemostatic pathway and, thus, not predispose to a higher bleeding risk [6,9]. However, in phase 3 trials, the magnitude M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 7 7 of the increased bleeding rates was much higher than expected on the basis of the preclinical and phases 2 trials, which suggested that vorapaxar did not significantly increase the risk of bleeding, over and above that of standard DAPT with aspirin and clopidogrel [6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigators reported that increasing the dose or adding antiplatelet agents resulted in stronger platelet inhibition without increasing the number of bleeding complications 8,10,19,20) . This seems slightly different from our major finding mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…Two phase II clinical trials showed that addition of vorapaxar to DAPT was associated with a reduction in adverse cardiac events without major side effects (57,58). However, in the phase III TRACER trial, vorapaxar significantly increased the risk of major bleeding and intracranial haemorrhage and was therefore stopped early (59).…”
Section: Presentmentioning
confidence: 99%